Influence of structural characteristics on sorption properties of lithium-selective composite materials based on TiO2 and MnO2 - M. O. Chaban; L. M. Rozhdestvenska; A. V. Palchik; V. M. Belyakov (Хімія, фізика та технологія поверхні)
Novel composite materials with equimolar ratio of TiO2 to MnO2 have been synthetized. Using the low-temperature N2 adsorption method their structural characteristics were calculated; and their influence on selectivity and kinetics of lithium sorption was shown. It was proved that sorption characteristics of the obtained materials are defermined by conditions of heat treatment during the synthesis. Higher temperatures provoke agglomeration of sorbent and decrease in its kinetic characteristics. At the same time, more lithium-selective sorption sites are formed and the selectivity of sorption increases. By the proposed synthesis method a highly selective to lithium ion-exchange material was obtained.